University as a City and University as a State: Methodological Tools of William Clark - V. K. Pichugina; Z. A. Lurie (Высшее образование в России)
William Clark’s methodological tools applied to the study of the history and philosophy of higher education are presented in a series of articles 1996-2003 and especially in his book “Academic Charisma and the Origins of the Research University” (2006). The last was a result of Clark’s long and accurate work in many areas of research, most of which have yet formed as academic fields. The author sets an ambitious task to examine evolution of academic practice (mainly German) as a process of bureaucratization and capitalization of education through the prism of academic charisma. Considering it as one of the types of legitimate dominance in the scientific world, W. Clark describes a scholar not in three spatial coordinates (of which he talks in the introduction), but in four: religion, politics, economics, and state/city. The last allows Clark to mark universities that accept or reject certain methods of transferring academic charisma on the educational landscape of the city. Another issue that is a key to the search of the basics of research university, is the question of the gradual suppression of oral culture by writing. In other words, how “say and be” (the phrase invented by the authors of this review) turned into “print or disappear” (aphorism cited many times by the author of the book). This question includes a number of others, which we point out analyzing the academic space, which, in the author’s mind, is broken up, collected and rebroken up into fragments of tables, catalogues, lists, statutes, tables, graphs, reports, questionnaires, dossiers, etc. Despite the fact that the translation of William Clark’s book into Russian was carried out in 2017, the methodology proposed is undeservedly little known to the researchers of higher education and, in general, has not received fundamental review in the scientific tradition. Its main provisions will be outlined in the framework of this article.